PENERAPAN GRAFIS PADA DESAIN GEROBAK PEDAGANG KULINER DI KAMPUNG LENGKONG KYAI - Kristanto, Desi Dwi; Nugraha, Hari; Pratama, Wahyudi; Leksono, Fitorio Bowo; Angelina, Donna (Jurnal Pengabdian dan Kewirausahaan, 2022)
Tangerang is a rapidly growing area with several locations becoming business and residential centers. In Bumi Serpong Damai (BSD) which is one of the areas that is the center of the crowd, there is a simple village called Lengkong Kyai who is a native of Serpong left among other elite settlements. Pembangunan Jaya University held Community Service activities to empower residents in Lengkong Kyai village who are Small, Micro, and Medium Enterprises (MSMEs) in the culinary field. One of the activities is making food carts with attractive designs. The design of this cart requires a different design approach so that it can display the characteristics of existing culinary products but still does not limit identity as a group because the use of this cart is not individually per resident, but is managed jointly by the existing merchant community.